Second-grade Difficulties in Understanding Place Value - Amelia, Nadya Ghassani; Herman, Tatang (International Conference on Elementary Education, 2024)
The concepts in mathematics education are interrelated and taught from the easiest one to the most difficult. One of the fundamental concepts taught to students is the concept of place value. If students do not understand place value, they will face difficulties in the following mathematics materials, especially in the topic of numbers. Therefore, this research aims to describe students' understanding and the mistakes they make in understanding the concept of place value. The research method used in this study is a descriptive method with a sample of 20 second-grade students. Based on the test results, 75% (15 students) have reached the minimum passing score with an average test score of 70, while 25% (5 students) scored below the average. To enhance students' understanding of place value, special attention is needed to ensure that no students find difficulties in said material. This research aims to assist teachers in anticipating students' understanding of the place value concept.